Study of constitutive relation of rail decarburized layer. (December 2021) - Zhao, Guotang; Chen, Shuai; Wu, Lei; Wen, Zefeng; Wang, Hengyu
Highlights: The constitutive relation of materials at different positions were obtained. A set of dimensionless functions were proposed for Material parameters. The Young's modulus and hardness decrease from the rail bulk to the surface. The reduction of hardness is mainly attributed to Young's modulus. Abstract: Rail decarburized layer has significant impact on the wear and rolling contact fatigue in the wheel-rail interaction. Due to the lack of constitutive relation of rail decarburized layer, it is impossible to analyse accurately the influence of rail decarburized layer on wheel-rail contact. To obtain the constitutive relation of this layer of decarburized non-uniform material, nano-indentation experiments were carried out at different vertical positions in the decarburization layer on a rail specimen with decarburization thickness of 0.55 mm. Young's modulus and hardness were determined using Oliver and Pharr method. Axisymmetric two-dimensional finite element models were established in ABAQUS to simulate the nano-indentation loading process and the power law elastic–plastic stress–strain relationships were obtained for material at different vertical positions in the rail decarburized layer. A set of dimensionless functions were proposed for Young's modulus, hardness, yield stress and strain hardening exponent at arbitrary depth in a rail decarburized layer or in a decarburized layer treated by rail pre-grinding. The results show that the Young's modulus and hardness decrease from the rail bulk to the surface of the decarburized layer. The Young's modulus and hardness near the surface are 11% and 35% lower than those in the rail bulk, respectively. However, the yield stress exhibits an increasing trend from rail bulk to the decarburized surface, where yield stress is 20% higher than the rail bulk. Analysis shows that the main reason that causes the reduction of hardness at the decarburized layer surface is the reduction of Young's modulus but not the yield stress.